Effect of the application of saline water on the irrigated soils of bacia Sucuru/Sumé, PB - Macêdo, Ladilson de Souza; dos Santos, José Bezerra (Pesquisa Agropecuaria Brasileira, 1992)
The temporal variability of salts in water irrigation and its effects on the soils of Bacia Sucuru, in Sumé, PB, Brazil, were evaluated through random sample stratified in eight lots farmers. The 264 soil and 88 water samples were collected during January 1987 to December 1989. The water presented increasing risk of saltiness at long time with high levels of sodium and chloride, 11.4 and 12.2 meq/l, respectively. The presence of non calcic brown and litolic soils in the captation area, as utilization of agricultural drainage water for irrigation impede the improvement of the water quality, predetermining the soils irrigated to alkalization. Among the crops explorated by irrigators only cotton is tolerant to saline concentration in the radicular zone. The significative presence of bicarbonate (2.68 to 3.80 meq/l) in the water restricts the practice of sprinkler irrigation over all due to conditions of high evaporation, local aridness and especific toxicity of sodium and chloride in sensible plants. The irrigated, soils classified as Alluvial-Eutrophic soils, presented decrease in salts due to normalization of the winter, principally to paralization of watering.